An advanced biomass gasification technology with integrated catalytic hot gas cleaning. Part III: Effects of inorganic species in char on the reforming of tars from wood and agricultural wastes - Zhang, S.; Song, Y.; Song, Y.; Yi, Q.; Dong, L.; Li, T.; Zhang, L.; Feng, J.; Li, W.; Li, Chun-Zhu (Elsevier Ltd, 2016)
Char is used directly as a catalyst for the catalytic reforming of tar during gasification. Experiments have been carried out to examine the effects of inorganics in char as a catalyst for the catalytic reforming of tar during the gasification of mallee wood, corn stalk and wheat straw in a pilot plant. The char catalyst was prepared from the pyrolysis of mallee wood at a fast heating rate. The catalytic activities of char and acid-washed char for tar reforming were compared under otherwise identical gasification conditions. For all biomass feedstocks tested for gasification, the tar contents in product gas could be drastically reduced by the catalyst, reaching a tar concentration level well below 100 mg/N m3. The acid-washed char also showed profound activity for tar reforming although its catalytic activity was definitely lower than the raw char. Both catalysts could effectively reform the aromatic ring systems (especially large aromatic ring systems with three or more fused benzene rings) in tars as is revealed using UV-fluorescence spectroscopy. The char itself was also partially gasified. After being used as a catalyst, the condensation of the aromatic rings and the accumulation of inorganic species led to drastic changes in char reactivity with O2 at 400 °C. The inorganic species in char tended to enhance the formation of H2 and CO during the reforming reactions in the catalytic reactor.